On Guided Imagery and Music (GIM) as Both Part of Music Therapy and as Separate From it - Lawes, Martin J (Voices: A World Forum for Music Therapy, 2022)
Guided Imagery and Music (GIM) can be considered a specialism in which qualified music therapists may train, along with mental health practitioners from other professional backgrounds including psychotherapists, psychologists, and psychiatrists. For this latter group of practitioners, identifying themselves as music therapists, or implying this when describing GIM as a music therapy method in advertising their services, is controversial. It may indeed even be unlawful in countries where music therapy training and practice are regulated by the state. The situation is a complex and inherently confusing one. This is because on the one hand GIM is an acknowledged international model of music therapy. On the other hand, as a specialism, GIM is distinct from music therapy in both training and practice, with GIM practitioners having various professional backgrounds. It is proposed that international collaboration and discussion are needed, with recommendations made to foster public confidence based on a clear understanding of who is and is not a qualified music therapist and member of the music therapy profession, and who is qualified to practice what safely and effectively. The article aims to illuminate the issues that may need to be taken into consideration in developing a consensus position.